Język w socjolekcie społeczności Black Pillu na portalu Wykop.pl = Language in the sociolect of the Black Pill community on Wykop.pl - Stawecki, Karol (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This paper touches upon the timely topic of the Black Pill community, which can be encountered on the internet page called Wykop.pl. One can observe that the Polish Internet users who contribute to the creation of Black Pill sociolect are strongly inspired by the vocabulary of the culture of the United States, where the Black Pill ideology stems from.
Keywords: socjolekt; Black Pill; Wykop; bańka informacyjna; sociolect; information bubble